A new species of fish belonging to of subgenus Spinibarbichthys (Spinibarbus: Cyprinidae: Cypriniformes) in Vietnam - Ngoc, Duong Quang; Duc, Nguyen Huu; Hau, Tran Duc (Academia Journal of Biology, 2014)
Nine species of the genus Spinibarbus Oshima, 1919 (Cyprinidae, Cypriniformes) are found in Vietnam, of which one is new species of subgenus Spinibarbichthys; distributed in China, Laos and North of Vietnam. The description of the new species and a key to identify the known species of subgenus Spinibarbichthys of Spinibarbus genus are given in the paper. New species name: Spinibarbus (Spinibarbichthys) maensis H. D. Nguyen, Q. N. Duong & D. H. Tran sp. nov. Holotyp: one scantling (female) is found in Ma river (Camthuy district, Thanhhoa province) of Vietnam. Paratyp: one scantling is found in Nganpho river (Huongson district, Hatinh province) of Vietnam. Etymology: the name maensis refers to the locality of this species. Description: body high and thin. Head high and short. Mouth subanterior. Two pair of barbels. Gill rakers on first arch 10. Last dorsal simple ray osseous, with 19 pair  serrae. Origin of dorsal fin behind of ventral fin and its origin near of origin of caudal fin than top of the nostril. Lateral line complete, pored scales in lateral series 27 - 28; Circumpeduncular scales 14, predorsal scales 8 + 5. Pharyngeal tooth three rows, 2.3.5-5.3.2. Coloration: body light roseate. Pectoral, ventral and anus fin are dark roseate. Distribution: lower and midle section of Ma and Nhatle rivers, Vietnam. Remarks: Spinibarbus (Spinibarbichthys) maensis sp. nov. is near with Spinibarbus (Spinibabichthys) denticulatus and Spinibarbus (Spinibarbichthys) namauensis by origin of dorsal fin behind of ventral fin. But there are some different characteristics: the number of lateral line scales are less, body is higher and thinner, head is higher in comparison with species Spinibarbus (Spinibarbichthys) denticulatus and Spinibarbus (Spinibarbichthys) namauensis. Spinibarbus (Spinibarbichthys)  maensis differed with Spinibarbus (Spinibarbichthys) sinensis and Spinibarbus (Spinibarbichthys) ovalius by: origin of dorsal fin, number of gill ranker of first branchial, number of scales in front of dorsal fin, head is shorter and higher.